A model for stud groups subjected to shear and moment. (1st June 2022) - Stanton, John F.; Calvi, Paolo M.
Highlights: Resistance of stud groups to eccentric shear includes friction and dowel action. Present models for combined loading require judgment and cannot be automated. This new model combines friction and dowel action. Shear resistance peaks in the middle of the shear-controlled region. Abstract: Steel members are often connected to reinforced concrete by means of headed studs embedded in the concrete. Several models are available for estimating the shear strength of such connections when they are subjected to pure shear loading, but guidance is lacking for the case of loading by shear and moment simultaneously. In this paper, a model is proposed for resistance to that combined loading. The shear resistance arises from both friction and dowel action (shear in the studs) while the moment is resisted by the couple formed by tension in the studs and compression across the steel–concrete interface. The distribution of shear and tension stresses in the different rows of studs is obtained uniquely and rationally through the use of the Lower Bound Theorem of plasticity, and requires no judgment by the user. Two regions of response, defined by the eccentricity of the load, are identified. It is shown that, in the shear-controlled region, the resistance rises to a peak that is significantly higher than that available if shear were resisted by friction alone. The model is tested by comparing its predictions with data from tests, and it achieves reasonable agreement. A discussion highlights some of the uncertainties and complexities in the physical behavior and the modeling challenges that they cause.